Proton beam therapy in apneic oxygenation treatment of an unresectable hepatocellular carcinoma: A case report and review of literature - Lin, Yi-Lan (World J Hepatol, 2018)
Presented here is the clinical course of a 63-year-old patient with a central, large and unresectable hepatocellular carcinoma (HCC) with liver metastases and tumor invasion of the portal and hepatic veins. After the tumor had been diagnosed, the patient was immediately treated with proton beam therapy (PBT), at a total dose of 60 Gy (relative biological effectiveness) in 20 fractions administered within 4 wk. To manage the respiratory movements, at the Rinecker Proton Therapy Center, apneic oxygenation was given daily, under general anesthesia. The patient tolerated both the PBT and general anesthesia very well, and did now show any signs of acute or late toxicity. The treatment was followed by constant reductions in the tumor marker alpha-fetoprotein and the cholestatic parameters gamma-glutamyltransferase and alkaline phosphatase. The patient commenced an adjuvant treatment with sorafenib, given at 6-wk intervals, after the PBT. Follow-up with regular magnetic resonance imaging has continued for 40 mo so far, demonstrating remarkable shrinkage of the HCC (maximal diameter dropping from approximately 13 cm to 2 cm). To date, the patient remains free of tumor recurrence. PBT served as a safe and effective treatment method for an unresectable HCC with vascular invasion.